Application of upflow anaerobic sludge blanket (UASB) reactor for food waste and pome treatment with biogas production - Muhammad Asif, Latif (2011)
The need for clean water is rising and anaerobic wastewater treatment can be used as a cost effective way out for biodegradation and energy production of organically polluted industrial waste streams. Indeed, the anaerobic digestion process can be applied to conduct various types of wastewaters in a more sustainable way than alternative processes. Applications comprise the treatment of municipal, industrial, agricultural and farming wastewaters. The upflow anaerobic sludge blanket (UASB) reactor is a system in which substrate passes first through an expanded sludge bed having a high concentration of biomass. Anaerobic treatment of liquidized food waste (LFW) was carried out in UASB reactor by stepwise increase in OLR and temperature. Thermophilic condition was achieved by increasing the temperature from 30-55 oC and pH was maintained at 7±0.5 throughout the experiment. Maximum COD removal efficiency was 93.67% (r=0.84) at an OLR of 12.5 g-COD/L.day and 4 days HRT. Maximum TOC removal efficiency was 79.14% (r=-0.94) at an influent TOC concentration of 3.59 g/L. Biogas and methane yield were recorded to a maximum of 1.364 L/g-CODremoved.day (r=0.81), 0.912 L/g-CODremoved.day (r=0.83) and average methane content of biogas was 63%. The reactor was fully acclimatized at 55oC and achieved stability with high removal efficiency and biogas production. An OLR of 12.5 g-COD/L.day and HRT of 4 days were suitable for the treatment of LFW in UASBR. The treatment process can also be extendable for more than ten weeks without any measurable problem. Anaerobic bach treatment of palm oil mill effluent (POME) was carried out with cement kiln dust (CKD) as neutrilizing agent. The UASB reactor was operated continuously at 35 °C for 41 days, with varying OLR from 1.5 to 4 g-COD/L.day at HRT. The digester pH was improved steadily by increasing CKD concentrations and 23-40 g-CaO/L of CKD dosage was found suitlable to maintan pH above 7.5. The correlation (r=0.78) between CKD dosage and reactor pH showed moderate to strong relationship between CKD and reactor pH. The maximum COD removal of 95% was obtained at 4 days HRT at a highest OLR of 4 g-COD/L.day (r=0.95). The suspended solids profile was drawn along four sampling ports of reactor with increasing CKD dosage and 80% removal of suspended silids was found at 37 g-CaO/L CKD dose (r=0.88) and biogas yield was 0.90 L/g-CODremoved.day. Overall performance of CKD showed satisfactory results by replacing expensive buffer solutions thus giving a new technique of neutrilizing the acidic wastewaters.